Road Surface Analysis Using the International Roughness Index and Pavement Condition Index (Case Study: Gajah Mada Street, Tegal City) - Marwanto, Riza Phahlevi; Maheswara, Andhika Adiwidya; Bahrelsi, Damar Risky; Perdana, Brezinka Ayu; Fitria, Ina; Hadi, Suprapto (Journal of Green Science and Technology, 2025)
Road surface quality plays an important role in ensuring safety and comfort for users Gajah Mada Street in Tegal City was chosen as the study site because it functions as a main route with heavy traffic flow, and there are various physical damages on its surface. This study aimed to evaluate the condition of the road by applying the International Roughness Index (IRI) and Pavement Condition Index (PCI) approaches. Data collection was conducted through field surveys using a Hawkeye vehicle for IRI and a visual PCI inspection based on ASTM D6433-11 standards. The analysis results showed an average PCI value of 77, categorized as very good, while the IRI value was 6.23 m/km, indicating a fair condition. The difference between the two methods highlights the importance of a multi-method approach in road condition assessment. This study recommends regular and periodic road maintenance to sustain optimal road performance.